Potencialidade de processamento industrial de cultivares de batatas - Garcia, Émerson Loli [UNESP]; do Carmo, Ezequiel Lopes; de Pádua, Joaquim Gonçalves; Leonel, Magali [UNESP] (FapUNIFESP (SciELO), 2015)
The industrialization of potato in Brazil has been limited because of the low availability of tubers with adequate quality, being supplied by imports of processed products demand. Eight cultivars of potato, adapted to the mountainous conditions of Minas Gerais state, harvest of 2011, were evaluated for their centesimal composition, color and amylose content.The results demonstrated that ‘Marcy’ and ‘Colorado’ cultivars showed important characteristic for cooking. The ‘Marlen’ and ‘Pirassu’ cultivars showed required attributes for processing in the form of chips or straw and the cultivar ‘BRS Ana’ for pre-fried sticks.
Industrial processing potential of potato cultivars
Keywords: Color; Fiber; Potato; Solanum tuberosum; Starch